Modified cerium oxide composite vanadium flow battery diaphragm and preparation method and application thereof

CN123033993APending Publication Date: 2026-11-03BAOTOU RESEARCH INSTITUTE OF RARE EARTHS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611109307.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing vanadium redox flow battery separators suffer from problems such as difficulty in balancing proton conductivity and vanadium ion permeability, poor dispersion of inorganic fillers, and weak interfacial bonding, resulting in poor battery performance.

Method used

Nano-sized cerium oxide was prepared by the sol-gel method and then modified by surface carboxylation and combined with sulfonated polyether ether ketone to form a modified cerium oxide and sulfonated polyether ether ketone composite film. The hydrogen bonding between the carboxyl group and the sulfonic acid group enhanced the interfacial bonding and dispersibility, achieving a balance between proton conductivity and vanadium blocking performance.

Benefits of technology

The composite membrane has improved proton conductivity and selective permeability, enhanced mechanical properties and long-term cycle stability, and solved the problems of high permeability, high cost and poor stability of traditional membranes in vanadium redox flow batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123033993A_ABST
    Figure CN123033993A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of modified cerium oxide composite vanadium flow battery diaphragm and its preparation method and application, belong to vanadium flow battery technical field, to solve at least one of the problems such as the proton conductivity and vanadium ion permeability of existing vanadium flow battery diaphragm are difficult to consider, the stability of existing inorganic filler modified diaphragm is poor.The carboxyl functional groups are introduced on the surface of carboxylated modified cerium oxide by the method of the present application, on the one hand, carboxyl can provide proton conduction sites, help to improve the overall proton conductivity of composite membrane, reduce the surface resistance of membrane;On the other hand, the steric hindrance effect and donnan repulsion of carboxyl can effectively block the positively charged vanadium ions from passing through the diaphragm, reduce the vanadium ion permeability, improve the selective permeability of diaphragm, and solve the problem that proton conductivity and vanadium resistance are difficult to consider.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium redox flow battery technology, and in particular to a modified cerium oxide composite vanadium redox flow battery separator, its preparation method, and its application. Background Technology

[0002] Vanadium redox flow batteries (VRFBs) are widely recognized as one of the most promising technologies for large-scale energy storage due to their high safety, long cycle life, and the ability to independently design power and capacity. The separator, as the core component of a vanadium redox flow battery, directly affects the battery's coulombic efficiency, energy efficiency, and cycle life. An ideal separator should possess both high proton conductivity (low sheet resistance) and low vanadium ion permeability (high selectivity).

[0003] While perfluorosulfonic acid membranes, exemplified by DuPont's Nafion membrane, possess high proton conductivity and chemical stability, their sulfonic acid groups exhibit a strong affinity for vanadium ions, leading to severe vanadium ion permeation, significant battery self-discharge, and decreased energy efficiency. Furthermore, the high cost of Nafion membranes severely restricts the large-scale application of VRFB (Vibration-Reduced Batteries). Non-fluorinated aromatic polymer membranes, such as sulfonated polyether ether ketone (SPEEK), offer lower costs (approximately 1 / 5 to 1 / 10 the cost of Nafion) and better vanadium blocking performance, their proton conductivity is positively correlated with the degree of sulfonation. High sulfonation levels result in excessive membrane swelling, leading to decreased mechanical properties and dimensional stability. Controlling membrane swelling and improving vanadium blocking performance while maintaining high proton conductivity remains a key technical challenge in this field. Additionally, the conductivity of composite membranes is improved by blending inorganic fillers with SPEEK.

[0004] However, the following common technical challenges still exist in the field of vanadium redox flow battery separators: it is difficult to balance proton conductivity and vanadium ion permeability; the inorganic filler has poor dispersibility and is prone to agglomeration in the polymer matrix; the interfacial bonding is weak, with a lack of chemical bonding between the inorganic and organic phases, resulting in poor long-term stability due to simple physical blending. Summary of the Invention

[0005] Based on the above analysis, the present invention aims to provide a modified cerium oxide composite vanadium redox flow battery separator, its preparation method and application, to solve at least one of the following problems: the difficulty in simultaneously achieving proton conductivity and vanadium ion permeability in existing vanadium redox flow battery separators, and the poor stability of existing inorganic filler-modified separators.

[0006] In a first aspect, the present invention provides a method for preparing a modified cerium oxide composite vanadium redox flow battery separator, comprising the following steps: S1: Nano-cerium oxide was prepared using the sol-gel method; S2: The nano-cerium oxide is modified by surface carboxylation to obtain modified cerium oxide with carboxyl groups grafted on the surface; S3: Sulfonate polyether ether ketone in concentrated sulfuric acid, and obtain sulfonated polyether ether ketone by precipitation, washing and drying; S4: The modified cerium oxide in S2 and the sulfonated polyether ether ketone in S3 are mixed evenly in an organic solvent, and a film is formed by solution casting and dried to obtain the diaphragm.

[0007] Furthermore, in S1, the sol-gel method specifically includes: dissolving soluble cerium salt and citric acid in water to obtain cerium salt solution and citric acid solution respectively; mixing the cerium salt solution and citric acid solution; adjusting the pH value to 7-8; heating to evaporate water to form a sol; allowing it to stand to obtain a gel; drying; calcining; and grinding to obtain nano-cerium oxide.

[0008] Furthermore, in S2, the surface carboxylation modification includes the following steps: (a) Disperse nano-cerium oxide in a mixed solution of ethanol and water, add vinyltrimethoxysilane, adjust the pH to 3.5-5.5 to carry out hydrolysis reaction, adjust the pH to 9-11 to carry out condensation reaction, and obtain vinylated cerium oxide; (b) The vinyl cerium oxide is dispersed in concentrated sulfuric acid, and potassium permanganate and sodium nitrate are added to carry out an oxidation reaction to obtain carboxylated cerium oxide.

[0009] Furthermore, in S3, the mass-volume ratio of polyetheretherketone to concentrated sulfuric acid is 10~20g:200~400mL.

[0010] Furthermore, in S3, the sulfonation reaction temperature is 30~60℃, and the sulfonation time is 1~6h.

[0011] Furthermore, in S4, the mass of the modified cerium oxide is 0.5 to 3.0% of the mass of the sulfonated polyether ether ketone.

[0012] Furthermore, in S4, the organic solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0013] Furthermore, in S4, the solution casting method includes pouring the well-mixed solution into a glass petri dish, placing it at room temperature for 12-24 hours, and then vacuum drying it at 60℃, 80℃, and 120℃ for 6-12 hours respectively.

[0014] Secondly, the present invention provides a battery separator prepared by the above method.

[0015] Thirdly, the present invention provides a vanadium redox flow battery, comprising a battery separator prepared by the above method.

[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. The method of this invention introduces a large number of carboxyl functional groups into the cerium oxide surface through carboxylation modification. On the one hand, carboxyl groups can provide proton conduction sites, which helps to improve the overall proton conductivity of the composite membrane and reduce the sheet resistance of the membrane. On the other hand, the steric hindrance effect of carboxyl groups and Donnan repulsion (repelling ions with the same charge and attracting ions with opposite charges, primarily attracting H+ ions with small hydrated size in the electrolyte) + The process continues until the charge inside the membrane reaches equilibrium, thus blocking the passage of vanadium ions with large hydrated sizes. This effectively blocks positively charged vanadium ions from passing through the membrane, reducing vanadium ion permeability and improving the selective permeability of the membrane. At the same time, it solves the problem of the difficulty in balancing proton conductivity and vanadium blocking performance.

[0017] 2. The carboxyl groups on the modified cerium oxide surface of this invention can form hydrogen bond interactions with the sulfonic acid groups of sulfonated polyether ether ketone, which improves the dispersibility of inorganic fillers in the polymer matrix, avoids the agglomeration of inorganic fillers, and enhances the interfacial bonding force between the inorganic and organic phases. Compared with composite membranes obtained by simple physical blending, the membrane obtained by this invention has better mechanical properties and long-term cycle stability.

[0018] 3. Due to the highly corrosive nature of sulfuric acid as the electrolyte in the vanadium redox flow battery operating system, and the unique problem of self-discharge caused by vanadium ion transmembrane permeation, this invention addresses the issue of high vanadium permeability and high cost associated with traditional perfluorosulfonic acid membranes used in vanadium redox flow batteries. This is achieved by using carboxyl-modified cerium oxide and sulfonated polyether ether ketone to form hydrogen bonds between carboxyl and sulfonic acid groups, thereby enhancing interfacial bonding stability. Simultaneously, the Donnan repulsion of carboxyl groups blocks the migration of positively charged vanadium ions. This solves the problems of high vanadium permeability and high cost associated with traditional perfluorosulfonic acid membranes used in vanadium redox flow batteries, and also overcomes the issues of easy agglomeration of fillers, inability to simultaneously achieve proton conductivity and vanadium barrier properties, and poor long-term cycle stability found in ordinary non-fluorinated blended membranes.

[0019] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description

[0020] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.

[0021] Figure 1 The infrared spectra of carboxylated cerium oxide (COOH-CeO2), sulfonated polyether ether ketone (SPEEK), and membrane (COOH-CeO2 / SPEEK) prepared in Example 1 of this invention are shown. Detailed Implementation

[0022] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.

[0023] A specific embodiment of the present invention discloses a method for preparing a modified cerium oxide composite vanadium redox flow battery separator, comprising the following steps: S1: Nano-cerium oxide was prepared using the sol-gel method; S2: The nano-cerium oxide is modified by surface carboxylation to obtain modified cerium oxide with carboxyl groups grafted on the surface; S3: The polyether ether ketone is sulfonated in concentrated sulfuric acid, and after precipitation, washing and drying, sulfonated polyether ether ketone (SPEEK) is obtained. S4: The modified cerium oxide in S2 and the sulfonated polyether ether ketone in S3 are mixed evenly in an organic solvent, and a film is formed by solution casting and dried to obtain the diaphragm.

[0024] Compared with existing technologies, the method of this invention introduces a large number of carboxyl functional groups into the cerium oxide surface through carboxylation modification. On the one hand, carboxyl groups can provide proton conduction sites, which helps to improve the overall proton conductivity of the composite membrane and reduce the sheet resistance of the membrane. On the other hand, the steric hindrance effect of carboxyl groups and Donnan repulsion (repelling ions with the same charge and attracting ions with opposite charges, primarily attracting H+ ions with small hydrated size in the electrolyte) + The process continues until the charge inside the membrane reaches equilibrium, thus blocking the passage of vanadium ions with large hydrated sizes. This effectively blocks positively charged vanadium ions from passing through the membrane, reducing vanadium ion permeability and improving the selective permeability of the membrane. At the same time, it solves the problem of the difficulty in balancing proton conductivity and vanadium blocking performance.

[0025] The modified cerium oxide surface carboxyl groups of this invention can form hydrogen bond interactions with the sulfonic acid groups of sulfonated polyether ether ketone, improving the dispersibility of inorganic fillers in the polymer matrix, avoiding the agglomeration of inorganic fillers, and enhancing the interfacial bonding force between the inorganic and organic phases. Compared with composite membranes obtained by simple physical blending, the membrane obtained by this invention has superior mechanical properties and long-term cycle stability.

[0026] The specific analysis is as follows: The hydrogen bonding between the -COOH group in the modified CeO2 and the -SO3H group in the sulfonated polyether ether ketone enhances the organic-inorganic interfacial bonding force, improving the mechanical properties and long-term stability of the composite membrane. This invention utilizes the oxygen vacancy characteristics of CeO2 to provide Grotthuss proton jumping sites, combined with the protonation effect of the carboxyl group, to construct a hydrogen bond network with SPEEK, thereby improving proton conductivity. Furthermore, through the dual mechanisms of the modified CeO2 steric hindrance effect and the Donnan repulsion effect, vanadium ion permeation is effectively suppressed. When the membrane of this invention is applied to vanadium redox flow batteries, its proton conductivity, vanadium permeability, tensile strength, and swelling ratio are all significantly improved compared to existing technologies.

[0027] Specifically, in S1, the sol-gel method includes: dissolving soluble cerium salt and citric acid in water to obtain cerium salt solution and citric acid solution respectively; mixing the cerium salt solution and citric acid solution; adjusting the pH value to 7-8; heating to evaporate water to form a sol; allowing it to stand to obtain a gel; drying; calcining; and grinding to obtain nano-cerium oxide.

[0028] Preferably, the molar concentration of the cerium salt solution is 0.30~0.65 mol / L, for example, 0.30 mol / L, 0.32 mol / L, 0.34 mol / L, 0.36 mol / L, 0.38 mol / L, 0.40 mol / L, 0.42 mol / L, 0.44 mol / L, 0.46 mol / L, 0.48 mol / L, 0.50 mol / L, 0.52 mol / L, 0.54 mol / L, 0.56 mol / L, 0.5 The molar concentrations of the citric acid solutions are 0.17~0.26 mol / L, for example, 0.17 mol / L, 0.18 mol / L, 0.19 mol / L, 0.20 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, and 0.26 mol / L.

[0029] Preferably, the molar ratio of citric acid in the citric acid solution to cerium in the cerium salt solution is 1:1 to 3:1, and the soluble cerium salt is Ce(NO3)3·6H2O.

[0030] It should be noted that stable citrate complexes can be formed within the above molar ratio range. If the molar ratio is lower than 1:1, cerium salt will remain in the system, resulting in a mixture with insufficient purity, which will lead to poor subsequent test results and decreased material performance. If the proportion of citric acid is excessive, organic matter cannot be fully burned off during calcination, and the final product will be black, which will also adversely affect the subsequent membrane preparation process. In addition, when the proportion of citric acid is excessive, the exothermic combustion during calcination is too intense, which can cause local overheating, leading to violent sintering and hard agglomeration of newly formed nanocrystals, resulting in uncontrolled particle size.

[0031] Preferably, the pH value is adjusted to 7-8 using ammonia water, and the mixture is stirred for 30 minutes to form a clear solution.

[0032] Preferably, the temperature for heating and evaporating water is 60~100℃, for example, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃.

[0033] Preferably, the settling time is 24 to 48 hours, for example, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 46 hours, and 48 hours.

[0034] Preferably, the drying temperature is 60~100℃, for example, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, and the drying time is 12~24h, for example, 12h, 14h, 16h, 18h, 20h, 22h, 24h.

[0035] Preferably, the calcination temperature is 500~700℃, for example, 500℃, 520℃, 540℃, 560℃, 580℃, 600℃, 620℃, 640℃, 660℃, 680℃, 700℃; the calcination time is 2~4h, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3.0h, 3.2h, 3.4h, 3.6h, 3.8h, 4h; and the heating rate is 2~ 5℃ / min, for example, 2℃ / min, 2.2℃ / min, 2.4℃ / min, 2.6℃ / min, 2.8℃ / min, 3.0℃ / min, 3.2℃ / min, 3.4℃ / min, 3.6℃ / min, 3.8℃ / min, 4.0℃ / min, 4.2℃ / min, 4.4℃ / min, 4.6℃ / min, 4.8℃ / min, 5℃ / min.

[0036] Preferably, the average particle size of the nano-cerium oxide is ≤40nm, and more preferably, the average particle size is 25~40nm, for example, 25nm, 27nm, 29nm, 31nm, 33nm, 35nm, 37nm, 39nm, or 40nm.

[0037] It should be noted that the smaller the nano-sized cerium oxide particles, the better. If the nano-sized cerium oxide particles are too large, the dispersion will be poor during the subsequent vinylation modification process, and the resulting product will be a mixture of partially modified cerium oxide and unmodified cerium oxide. Furthermore, in the subsequent film formation process, excessively large particle size will also have an adverse effect on the swelling rate and vanadium ion permeability of the membrane.

[0038] Specifically, in S2, the surface carboxylation modification includes the following steps: (a) Disperse nano-cerium oxide in a mixed solution of ethanol and water, add vinyltrimethoxysilane, adjust the pH to 3.5-5.5 (e.g., 3.5, 3.7, 3.9, 4.1, 4.3, 4.5, 4.7, 4.9, 5.1, 5.3, 5.5) to carry out a hydrolysis reaction, and adjust the pH to 9-11 (e.g., 9, 9.5, 10, 10.5, 11) to carry out a condensation reaction to obtain vinylated cerium oxide; (b) The vinyl cerium oxide is dispersed in concentrated sulfuric acid, and potassium permanganate and sodium nitrate are added to carry out an oxidation reaction to obtain carboxylated cerium oxide (modified cerium oxide).

[0039] Specifically, in step (a), the mass-to-volume ratio of nano-cerium oxide to the mixed solution is 1-5g (e.g., 1g, 2g, 3g, 4g, 5g): 50-200mL (50mL, 60mL, 70mL, 80mL, 90mL, 100mL, 110mL, 120mL, 130mL, 140mL, 150mL, 160mL, 170mL, 180mL, 190mL, 200mL), and the volume ratio of ethanol to water is 1:1-4:1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1.

[0040] Specifically, in step (a), the mass ratio of nano-cerium oxide to vinyltrimethoxysilane is 1 to 5 (e.g., 1, 2, 3, 4, 5): 2 to 10 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10).

[0041] Specifically, in step (a), glacial acetic acid is used to adjust the pH value to 3.5~5.5, for example, 3.5, 3.7, 3.9, 4.1, 4.3, 4.5, 4.7, 4.9, 5.1, 5.3, 5.5, and ammonia is used to adjust the pH value to 9~11, for example, 9, 9.5, 10, 10.5, 11.

[0042] Specifically, in step (a), the hydrolysis reaction is carried out at a temperature of 20-30°C, for example, 20°C, 22°C, 24°C, 26°C, 28°C, or 30°C, for a time of 0.5-1 h, for example, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, or 1 h. The condensation reaction is carried out at a temperature of 60-80°C, for example, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, or 80°C, for a time of 2-4 h, for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, or 4 h.

[0043] Specifically, in step (b), the mass-to-volume ratio of the cerium vinylidene oxide to concentrated sulfuric acid is 0.5~2 g (e.g., 0.5g, 0.6g, 0.7g, 0.8g, 0.9g, 1.0g, 1.1g, 1.2g, 1.3g, 1.4g, 1.5g, 1.6g, 1.7g, 1.8g, 1.9g, 2g): 20~50 mL (e.g., 20mL, 25mL, 30mL, 35mL, 40mL, 45mL, 50mL), the mass ratio of cerium vinyl oxide, potassium permanganate, and sodium nitrate is 0.5~2 (e.g., 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2): 0.9~3.6 (e.g., 0.9, 1.1, 1.3, 1.5, 1.7, 1.9, 2.1, 2.3, 2.5, 2.7, 2.9, 3.1, 3.3, 3.5, 3.6): 0.15~0.6 (e.g., 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6).

[0044] Specifically, in step (b), the temperature of the oxidation reaction is 60~100℃, for example, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, and the reaction time is 2~6h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h.

[0045] It should be noted that the present invention performs surface carboxylation modification on nano-cerium oxide, so that the surface of CeO2 carries -COOH groups, which form a strong interaction with the -SO3H groups of SPEEK, thereby achieving uniform dispersion of CeO2 in the SPEEK matrix and avoiding agglomeration.

[0046] Specifically, in S3, the mass and volume of polyetheretherketone and concentrated sulfuric acid are 10~20g (e.g., 10g, 12g, 14g, 16g, 18g, 20g): 200~400mL (e.g., 200mL, 220mL, 240mL, 260mL, 280mL, 300mL, 320mL, 340mL, 360mL, 380mL, 400mL).

[0047] Specifically, in S3, the sulfonation reaction temperature is 30~60℃, for example, 30℃, 32℃, 34℃, 36℃, 38℃, 40℃, 42℃, 44℃, 46℃, 48℃, 50℃, 52℃, 54℃, 56℃, 58℃, 60℃, and the sulfonation time is 1~6h, for example, 1h, 2h, 3h, 4h, 5h, 6h.

[0048] Specifically, in S4, the mass of the modified cerium oxide is 0.5 to 3.0% of the mass of the sulfonated polyether ether ketone, for example, 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.1%, 2.3%, 2.5%, 2.7%, 2.9%, 3.0%.

[0049] It should be noted that the modified cerium oxide content is chosen in this invention because if the amount of modified cerium oxide added is too low, the carboxyl groups cannot fully provide proton conduction sites and block vanadium ions, resulting in limited improvement in membrane performance. If the amount added is too high, the modified cerium oxide is still prone to agglomeration, which not only destroys the integrity of the organic-inorganic interface but also increases internal defects in the membrane, leading to a decrease in proton conductivity and an increase in vanadium ion permeability, thus reducing the overall performance of the membrane. This invention selects an addition amount of 0.5-3.0%, which ensures that the carboxyl groups can fully function to build a complete hydrogen-bonded proton conduction network while maintaining good dispersion of the modified cerium oxide in the sulfonated polyether ether ketone matrix, ensuring interfacial bonding, and achieving a balance between proton conductivity and vanadium blocking performance, resulting in a composite membrane with excellent overall performance.

[0050] Preferably, in S4, the organic solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0051] Specifically, in S4, the solution casting method involves pouring the well-mixed solution into a glass petri dish and placing it at room temperature for 12-24 hours, for example, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, and 24 hours, and then vacuum drying it at 60°C, 80°C, and 120°C for 6-12 hours, for example, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, and 12 hours.

[0052] It should be noted that the present invention employs gradient drying because the casting solution contains a large amount of organic solvents (N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide): if dried directly, the surface solvent will evaporate and shrink rapidly, which can easily cause the membrane to curl, crack or bubble; if the low-temperature evaporation step is skipped, a dense hard skin will first form on the membrane surface, blocking the evaporation channels of the internal solvent. Subsequently, the internal solvent will vaporize and expand, which will directly cause bubbling and delamination problems.

[0053] In this invention, the hydrogen bonding between the -COOH group on the modified cerium oxide surface and the -SO3H group in sulfonated polyether ether ketone enhances the organic-inorganic interfacial bonding, thereby improving the mechanical properties and long-term stability of the membrane. The method utilizes the oxygen vacancy characteristics of CeO2 to provide Grotthuss proton jumping sites, combined with the protonation of carboxyl groups, to construct a hydrogen bond network with SPEEK, reducing the proton conduction activation energy and improving proton conductivity. The membrane prepared by this invention effectively inhibits vanadium ion permeation and reduces vanadium ion permeability through a dual mechanism of physical barrier and Donnan repulsion. The doping of modified CeO2 reduces the swelling ratio of the membrane, improving dimensional and chemical stability.

[0054] The method of the present invention is simple in process, low in raw material cost, and suitable for large-scale production.

[0055] Another specific embodiment of the present invention discloses a modified cerium oxide composite vanadium redox flow battery separator prepared by the above method.

[0056] Another specific embodiment of the present invention discloses a vanadium redox flow battery, comprising the above-described modified cerium oxide composite vanadium redox flow battery separator.

[0057] Because sulfuric acid, the electrolyte in vanadium redox flow batteries, is highly corrosive, and vanadium ions permeate across the membrane, leading to self-discharge, this invention addresses the issue of high vanadium permeability and high cost associated with traditional perfluorosulfonic acid membranes used in vanadium redox flow batteries. This is achieved by using carboxyl-modified cerium oxide and sulfonated polyether ether ketone (PEEK) to form hydrogen bonds between carboxyl and sulfonic acid groups, thereby enhancing interfacial stability. Simultaneously, the Donnan repulsion of carboxyl groups blocks the migration of positively charged vanadium ions. This solution addresses the problems of high vanadium permeability and high cost associated with traditional perfluorosulfonic acid membranes in vanadium redox flow batteries, while also overcoming the issues of easy agglomeration of fillers, the inability to simultaneously achieve both proton conductivity and vanadium barrier properties, and poor long-term cycle stability in ordinary non-fluorinated blended membranes.

[0058] The technical solution of the present invention will be further explained below with reference to specific embodiments.

[0059] Example 1 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment includes the following steps: S1: Preparation of nano-cerium oxide by sol-gel method: Ce(NO3)3·6H2O and citric acid were dissolved in water to obtain cerium salt solution with a molar concentration of 0.50 mol / L and citric acid solution with a molar concentration of 0.22 mol / L, respectively. The cerium salt solution and citric acid solution were mixed, and the molar ratio of citric acid to cerium in the cerium salt solution was 2:1. The pH value was adjusted to 7.5 with ammonia water, and the mixture was stirred for 30 min to form a clear solution. The solution was heated to 80℃ to evaporate the water to form a sol. After standing for 36 h, a gel was obtained. The gel was dried at 100℃ for 18 h and calcined at 600℃ for 3 h with a heating rate of 2℃ / min. After grinding, nano-cerium oxide with an average particle size of 25 nm was obtained. S2: Preparation of modified cerium oxide: (a) Disperse nano-cerium oxide in a mixed solution of ethanol and water, with a mass-to-volume ratio of nano-cerium oxide to the mixed solution of 2.5 g: 150 mL and a volume ratio of ethanol to water of 1:1. Add vinyltrimethoxysilane, with a mass ratio of nano-cerium oxide to vinyltrimethoxysilane of 3:6. Adjust the pH to 4 with glacial acetic acid to carry out a hydrolysis reaction at a temperature of 25 °C for 45 min. Adjust the pH to 10 with ammonia to carry out a condensation reaction at a temperature of 70 °C for 3 h to obtain vinylated cerium oxide. (b) The vinyl cerium oxide was dispersed in concentrated sulfuric acid at a mass-to-volume ratio of 1 g:30 mL. Potassium permanganate and sodium nitrate were added for oxidation reaction at a mass ratio of 1 g:1.8 g:0.3 g. The oxidation reaction was carried out at a temperature of 80 °C for 4 h. The mixture was washed until neutral and dried at 60 °C to obtain carboxylated cerium oxide (COOH-CeO2).

[0060] S3: Polyether ether ketone (PEEEK) is sulfonated in concentrated sulfuric acid at a mass-volume ratio of 10 g to 200 mL. The sulfonation reaction is carried out at a temperature of 45 °C for 3.5 h. The reaction solution is then slowly poured into an ice-water mixture to precipitate the precipitate. The precipitate is washed with deionized water until neutral and dried at 60 °C for 24 h to obtain sulfonated PEEK. S4: The modified cerium oxide from S2 and the sulfonated polyether ether ketone from S3 are mixed evenly in the organic solvent N,N-dimethylacetamide. The mass of the modified cerium oxide is 1.0% of the mass of the sulfonated polyether ether ketone. The evenly mixed solution is poured into a glass petri dish and placed at room temperature for 18 hours. Then, it is vacuum dried at 60°C, 80°C, and 120°C for 9 hours each. The glass petri dish is then immersed in deionized water, and the membrane is peeled off to obtain the diaphragm (COOH-CeO2 / SPEEK).

[0061] The infrared spectra of the carboxylated cerium oxide (COOH-CeO2), sulfonated polyether ether ketone (SPEEK), and membrane (COOH-CeO2 / SPEEK) prepared in this embodiment are as follows: Figure 1 As shown, the COOH-CeO2 / SPEEK membrane retains both SPEEK and COOH-CeO2 characteristic peaks, proving successful cerium carboxyl oxide doping. The OH vibration peak in the sulfonic acid group of pure SPEEK is at 3428 cm⁻¹. –1 The O–H vibration of the COOH-CeO2 / SPEEK composite membrane was at 3308 cm⁻¹. -1 A significant red shift and peak broadening occurred, due to the formation of numerous intermolecular hydrogen bonds between the carboxyl groups and sulfonic acid groups on the CeO2 surface; this membrane exhibits a higher concentration of sulfonic acid groups (1076 cm⁻¹) compared to pure SPEEK. -1 (O=S=O), 706 cm -1 (SO) all showed a slight redshift, confirming Ce 4+ It exhibits interfacial coordination interactions with sulfonic acid oxygen. CeO2-COOH originally had a 1632 cm⁻¹ -1 The free carboxyl C=O peak disappears at 1530 and 1445 cm⁻¹. -1 The formation of a carboxylate stretching double peak indicates that the carboxyl group reacts with Ce. 4+ Coordination occurs.

[0062] Example 2 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment includes the following steps: S1: Preparation of nano-cerium oxide by sol-gel method: Ce(NO3)3·6H2O and citric acid were dissolved in water to obtain cerium salt solution with a molar concentration of 0.30 mol / L and citric acid solution with a molar concentration of 0.17 mol / L, respectively. The cerium salt solution and citric acid solution were mixed, and the molar ratio of citric acid to cerium in the cerium salt solution was 1:1. The pH value was adjusted to 7 with ammonia water, and the mixture was stirred for 30 min to form a clear solution. The solution was heated to 60℃ to evaporate the water to form a sol. After standing for 48 h, a gel was obtained. The gel was dried at 80℃ for 24 h and calcined at 500℃ for 4 h with a heating rate of 5℃ / min. After grinding, nano-cerium oxide with an average particle size of 35 nm was obtained. S2: Preparation of modified cerium oxide: (a) Disperse nano-cerium oxide in a mixed solution of ethanol and water, with a mass-to-volume ratio of nano-cerium oxide to the mixed solution of 1 g: 200 mL and a volume ratio of ethanol to water of 2:1. Add vinyltrimethoxysilane, with a mass ratio of nano-cerium oxide to vinyltrimethoxysilane of 1:10. Adjust the pH to 3.5 with glacial acetic acid and carry out a hydrolysis reaction at a temperature of 20 °C for 1 h. Adjust the pH to 9 with ammonia water and carry out a condensation reaction at a temperature of 60 °C for 4 h to obtain vinylated cerium oxide. (b) The vinyl cerium oxide was dispersed in concentrated sulfuric acid at a mass-to-volume ratio of 0.5 g: 20 mL. Potassium permanganate and sodium nitrate were added to carry out an oxidation reaction at a mass ratio of 0.5:0.9:0.15. The oxidation reaction was carried out at a temperature of 60 °C for 6 h. The mixture was washed until neutral and dried at 60 °C to obtain carboxylated cerium oxide.

[0063] S3: Polyether ether ketone is sulfonated in concentrated sulfuric acid at a mass-volume ratio of 15g:300mL. The sulfonation reaction is carried out at a temperature of 30℃ for 6 hours. The reaction solution is then slowly poured into an ice-water mixture for precipitation, washed with deionized water until neutral, and dried at 60℃ for 24 hours to obtain sulfonated polyether ether ketone (SPEEK). S4: The carboxylated cerium oxide from S2 and the sulfonated polyether ether ketone from S3 are mixed evenly in the organic solvent N-methylpyrrolidone, wherein the mass of the carboxylated cerium oxide is 0.5% of the mass of the sulfonated polyether ether ketone. The evenly mixed solution is poured into a glass culture dish and placed at room temperature for 12 hours. Then, it is vacuum dried at 60°C, 80°C, and 120°C respectively. After 6 hours, the glass culture dish is immersed in deionized water, and the membrane is peeled off to obtain the diaphragm.

[0064] Example 3 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment includes the following steps: S1: Preparation of nano-cerium oxide by sol-gel method: Ce(NO3)3·6H2O and citric acid were dissolved in water to obtain cerium salt solution with a molar concentration of 0.65 mol / L and citric acid solution with a molar concentration of 0.26 mol / L, respectively. The cerium salt solution and citric acid solution were mixed, and the molar ratio of citric acid to cerium in the cerium salt solution was 3:1. The pH value was adjusted to 8 with ammonia water, and the mixture was stirred for 30 min to form a clear solution. The solution was heated to 100℃ to evaporate the water to form a sol. After standing for 24 h, a gel was obtained. The gel was dried at 60℃ for 12 h and calcined at 700℃ for 2 h with a heating rate of 2℃ / min. After grinding, nano-cerium oxide with an average particle size of 40 nm was obtained. S2: Preparation of modified cerium oxide: (a) Disperse nano-cerium oxide in a mixed solution of ethanol and water, with a mass-to-volume ratio of nano-cerium oxide to the mixed solution of 5 g: 50 mL and a volume ratio of ethanol to water of 4: 1. Add vinyltrimethoxysilane, with a mass ratio of nano-cerium oxide to vinyltrimethoxysilane of 5: 2. Adjust the pH to 5.5 with glacial acetic acid to carry out a hydrolysis reaction at a temperature of 30 °C for 30 min. Adjust the pH to 11 with ammonia to carry out a condensation reaction at a temperature of 80 °C for 2 h to obtain vinylated cerium oxide. (b) The vinyl cerium oxide was dispersed in concentrated sulfuric acid at a mass-to-volume ratio of 2 g:50 mL. Potassium permanganate and sodium nitrate were added to carry out an oxidation reaction at a mass ratio of 2:3.6:0.6. The oxidation reaction was carried out at a temperature of 100 °C for 2 h. The mixture was washed until neutral and dried at 60 °C to obtain carboxylated cerium oxide.

[0065] S3: Polyether ether ketone is sulfonated in concentrated sulfuric acid at a mass-volume ratio of 20g:400mL. The sulfonation reaction is carried out at a temperature of 60℃ for 1h. The reaction solution is then slowly poured into an ice-water mixture for precipitation, washed with deionized water until neutral, and dried at 60℃ for 24h to obtain sulfonated polyether ether ketone (SPEEK). S4: The carboxylated cerium oxide from S2 and the sulfonated polyether ether ketone from S3 are mixed evenly in the organic solvent dimethyl sulfoxide, wherein the mass of the carboxylated cerium oxide is 3.0% of the mass of the sulfonated polyether ether ketone. The evenly mixed solution is poured into a glass culture dish and placed at room temperature for 24 hours. Then, it is vacuum dried at 60°C, 80°C, and 120°C for 12 hours respectively. The glass culture dish is then immersed in deionized water, and the membrane is peeled off to obtain the diaphragm.

[0066] Example 4 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment is similar to that in Example 1, except that in S4, the mass of the carboxylated cerium oxide is 0.5% of the mass of the sulfonated polyether ether ketone.

[0067] Example 5 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment is similar to that in Example 1, except that in S4, the mass of the carboxylated cerium oxide is 3.0% of the mass of the sulfonated polyether ether ketone.

[0068] Comparative Example 1 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment is similar to that in Example 1, except that steps S2 and S4 are omitted, and the nano-cerium oxide prepared in S1 is mixed evenly with sulfonated polyether ether ketone in the organic solvent N,N-dimethylacetamide.

[0069] Comparative Example 2 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment is similar to that in Example 1, except that steps S1 and S2 are omitted, and sulfonated polyether ether ketone is directly cast into a film.

[0070] Comparative Example 3 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment is similar to that in Example 1, except that in S4, the mass of the carboxylated cerium oxide is 0.4% of the mass of the sulfonated polyether ether ketone.

[0071] Comparative Example 4 The preparation method of the modified cerium oxide composite vanadium redox flow battery separator in this embodiment is similar to that in Example 1, except that in S1, the molar ratio of citric acid in the citric acid solution to cerium in the cerium salt solution is 0.5:1.

[0072] Experimental Example 1 The proton conductivity, vanadium permeability, tensile strength, and swelling ratio of the modified cerium oxide composite vanadium redox flow battery membranes prepared in the examples and comparative examples were tested respectively. The results are shown in Table 1. The test conditions for each property are as follows: (1) Proton conductivity: The test temperature was room temperature; (2) Vanadium permeability: Vanadium flow batteries were prepared using the membranes prepared in the examples and comparative examples, respectively, and 3 mol L... –1 1.5 mol L of H2SO4 –1 VOSO4 solution and 3 mol L –1 1.5 mol L of H2SO4 –1 The MgSO4 solution was separated into two sides by a test diaphragm. The MgSO4 solution with the same concentration as VOSO4 was mainly used to balance the concentration difference caused by VOSO4. The volumes of the solutions on both sides were equal, each 70 mL. The concentration of vanadium ions on the side without vanadium ions was tested every 6 hours, for a total of 28 tests.

[0073] (3) Tensile strength: The diaphragms prepared in the examples and comparative examples were cut into 40mm×10mm sizes and tested using an electronic universal testing machine (CMT4502, MTS). The tensile test speed of the testing machine was 5 mm / min. The length of 10mm at each end of the sample membrane was used for clamping and fastening. The length of the part to be tested was 20mm×10mm.

[0074] (4) Swelling rate: The diaphragms prepared in the examples and comparative examples were dried, and the dried diaphragms were cut into rectangular samples. The length of the sample was recorded as L. dry Immerse the sample completely in deionized water until it becomes saturated and stops absorbing water. Remove the sample and quickly dry its surface with absorbent paper. Measure and record the length L after immersion. wet The swelling ratio is calculated using the following formula.

[0075] Swelling rate = ×100%; Among them, L dry and L wet These represent the lengths of the tested diaphragm sample before and after immersion, respectively. The difference between the two is the amount of expansion of the diaphragm after immersion.

[0076] Table 1

[0077] The proton conductivity of the membrane in this invention is ≥100 mS·cm -1 Vanadium permeability ≤ 9.5 × 10 -7 cm 2 / min, tensile strength ≥69.48MPa, swelling rate ≤9.7%.

[0078] The test results show that the composite films prepared in Examples 1-5 of this invention are superior to those in Comparative Examples 1-4 in terms of conductivity, vanadium permeability, tensile strength, and swelling ratio, achieving both high proton conductivity and improved vanadium blocking performance. Tensile strength is related to the amount of doped modified cerium oxide; the more doped, the greater the tensile strength. This is because inorganic materials typically have high hardness and rigidity, and doping them into SPEEK can significantly improve the overall rigidity and hardness of SPEEK. Swelling ratio and vanadium permeability are related to the cerium oxide nanoparticles and the amount of doped modified cerium oxide. Smaller cerium oxide particles result in lower swelling ratio and vanadium permeability; a larger amount of doped modified cerium oxide leads to a larger swelling ratio. The oxygen vacancy characteristics of modified cerium oxide provide Grotthuss proton jumping sites, which, combined with the protonation of carboxyl groups, form a hydrogen bond network with SPEEK, accelerating proton conductivity. Therefore, the more modified cerium oxide added, the greater the proton conductivity, but this also increases the swelling ratio and vanadium ion permeability.

[0079] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a modified cerium oxide composite vanadium redox flow battery separator, characterized in that, Includes the following steps: S1: Nano-cerium oxide was prepared using the sol-gel method; S2: The nano-cerium oxide is modified by surface carboxylation to obtain modified cerium oxide with carboxyl groups grafted on the surface; S3: Sulfonate polyether ether ketone in concentrated sulfuric acid, and obtain sulfonated polyether ether ketone by precipitation, washing and drying; S4: The modified cerium oxide in S2 and the sulfonated polyether ether ketone in S3 are mixed evenly in an organic solvent, and a film is formed by solution casting and dried to obtain the diaphragm.

2. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to claim 1, characterized in that, In S1, the sol-gel method specifically includes: dissolving soluble cerium salt and citric acid in water to obtain cerium salt solution and citric acid solution respectively; mixing the cerium salt solution and citric acid solution; adjusting the pH value to 7-8; heating to evaporate water to form a sol; allowing it to stand to obtain a gel; drying; calcining; and grinding to obtain nano-cerium oxide.

3. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to claim 1, characterized in that, In S2, the surface carboxylation modification includes the following steps: (a) Disperse nano-cerium oxide in a mixed solution of ethanol and water, add vinyltrimethoxysilane, adjust the pH to 3.5-5.5 to carry out hydrolysis reaction, adjust the pH to 9-11 to carry out condensation reaction, and obtain vinylated cerium oxide; (b) The vinyl cerium oxide is dispersed in concentrated sulfuric acid, and potassium permanganate and sodium nitrate are added to carry out an oxidation reaction to obtain carboxylated cerium oxide.

4. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to any one of claims 1-3, characterized in that, In S3, the mass-volume ratio of polyetheretherketone to concentrated sulfuric acid is 10~20g:200~400mL.

5. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to any one of claims 1-3, characterized in that, In S3, the sulfonation reaction temperature is 30~60℃ and the sulfonation time is 1~6h.

6. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to any one of claims 1-3, characterized in that, In S4, the mass of the modified cerium oxide is 0.5 to 3.0% of the mass of the sulfonated polyether ether ketone.

7. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to claim 1, characterized in that, In S4, the organic solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

8. The method for preparing a modified cerium oxide composite vanadium redox flow battery separator according to claim 1, characterized in that, In S4, the solution casting method involves pouring the well-mixed solution into a glass petri dish, placing it at room temperature for 12-24 hours, and then vacuum drying it at 60℃, 80℃, and 120℃ for 6-12 hours respectively.

9. A battery separator prepared by the method according to any one of claims 1-8.

10. A vanadium redox flow battery, characterized in that, This includes battery separators prepared by any one of claims 1-8.